2003
DOI: 10.1001/jama.290.16.2168
|View full text |Cite
|
Sign up to set email alerts
|

Bile Duct Injury During Cholecystectomy and Survival in Medicare Beneficiaries

Abstract: Context Common bile duct (CBD) injury during cholecystectomy is a significant source of patient morbidity, but its impact on survival is unclear. Objective To demonstrate the relation between CBD injury and survival and to identify the factors associated with improved survival among Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
275
6
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(302 citation statements)
references
References 38 publications
8
275
6
13
Order By: Relevance
“…BDIs may hence lead to prolonged morbidity, high costs, and an impaired quality of life. [1][2][3] An optimization of the management strategy can reduce these complications.…”
Section: Discussionmentioning
confidence: 99%
“…BDIs may hence lead to prolonged morbidity, high costs, and an impaired quality of life. [1][2][3] An optimization of the management strategy can reduce these complications.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The variation in frequency in the literature is mainly due to various ways of defining a BDI, i.e. if leakage from the cystic duct and liver bed is classified as a bile duct injury or not.…”
Section: Introductionmentioning
confidence: 99%
“…BDI causes serious consequences for the patient, which is compounded by any delay in the recognition of an insult or if a repair is attempted by an inexperienced surgeon [33]. Several authors have reported alarming outcomes for BDI repair, and in some series, mortality and morbidity for biliodigestive reconstruction after injury are as high as 8.6 % and 42 % respectively [34].…”
mentioning
confidence: 99%